(untitled) (Medico Legal Update, 2020)
Photoaging is an extrinsic skin aging caused by ultraviolet radiation. It may affect patients’ quality of life. Ultraviolet radiation causes increasing of Kelch-like ECH-associating protein1-nuclear factor erythoid 2-related factor 2 (Keap1-Nrf2) protein, that plays role in photoaging pathogenesis. Many substances, such as green tea catechins, have been developed in photoaging prevention. The most abundant catechin in green tea is epigallocatechin-3-gallate (EGCG). This study was an in silico study, aimed to obtain the effectiveness of EGCG through molecular docking on Keap1-Nrf2 protein. The bioinformatics tools used in this study, were Protein Data Bank (PDB), ChemDraw, Chem3D, and Molegro Virtual Docker (MVD) software. Mol Dock and ReRank score was evaluated in this study, reflected the interaction between Keap1-Nrf2 protein and compound molecules. The prediction of EGCG pharmacokinetics were performed using pkCSM On Line Tool. The result of molecular docking between Keap1-Nrf2 protein with a candidate ligand (EGCG), a control ligand (arbutin), and a reference ligand (FB2_1615[A]) using MVD software, showed that the binding affinity of Keap1-Nrf2 protein with EGCG to be the lowest. The prediction of skin permeability of EGCG using pkCSM On-Line Tool was -2.735 cm/h and it was predicted that EGCG did not cause skin sensitization and AMES toxicity. EGCG has higher potential than arbutin and reference ligand to be an alternative agent in photoaging prevention. EGCG was predicted to have good skin absorption profile, without toxicity effect.